Extraction and physico-chemical characterization of water-soluble polysaccharides from Opuntia dillenii (Ker Gawl.) Haw. Cladodes - Nguyen, Thi-Hong-An; Dung, Hoang Thi Kim; Nguyen, Thi-Thuy-Huong (Vietnam Journal of Science and Technology, 2021)
Opuntia dillenii (Ker Gawl.) Haw., a well-known member of the Cactaceae family, played an important role in agriculture and medicine. In this study, the extraction conditions and the physico-chemical properties of water-soluble polysaccharides (OMP) from Opuntia dillenii mucilage were investigated. The cactus cladodes used in the study were collected from Binh Thuan province, Vietnam. The optimum extraction conditions of water extraction with conventional heating included at temperature 70oC in 120 min. The crude and deproteinized polysaccharides yield were 17.7 % and 7.9 %. By analysis of gel permeation chromatography (GPC), the study showed that the polysaccharides possessed a low average molecular weight (129,681 Da). In addition, the characterization of polysaccharide was determined by Fourier-Transform Infrared Spectroscopy (FTIR), and High-Performance Liquid Chromatography (HPLC). The results indicated that the types of sugars in the water-soluble polysaccharides extracted